Editorial – Revista Ambiente Contábil – Volume 17 – Número 1 – Ano 2025 (Jan./Jun. 2025) - Prof. Dr. Maurício Corrêa da Silva (Revista Ambiente Contábil)
Editorial – Revista Ambiente Contábil – Volume 17 – Número 1 – Ano 2025 (Jan./Jun. 2025)